Formulasi dan Evaluasi Lotion Gel Ekstrak Etanol Daun Tapak Dara (Catharanthus roseus L.) Sebagai Tabir Surya: Evaluation of Ethanol Extract Gel Lotion of Tapak Dara Leaves (Catharanthus roseus L.) as a Sunscreen - Muna, Nadia Nailul; Bari, Akhmad Al; Basith, Abdul; Qoriati, Yani’ (Jurnal Inovasi Farmasi Indonesia (JAFI), 2025)
Ultraviolet (UV) radiation exposure can lead to various skin disorders, ranging from irritation to cancer. One preventive measure is the use of natural-based sunscreens, which are considered safer. Tapak dara leaves (Catharanthus roseus L.) contain flavonoids, saponins, and alkaloids with potential UV-protective properties. This study aimed to formulate an ethanol extract gel lotion of tapak dara leaves and evaluate its Sun Protection Factor (SPF). The extract was obtained via maceration and formulated into three concentrations (2%, 3%, and 4%). The formulations were assessed through organoleptic testing, homogeneity, pH, spreadability, adhesiveness, and SPF value using UV-Vis spectrophotometry. All formulations met acceptable physical standards, with SPF values ranging from 9.865 to 12.012. The highest SPF was observed in formula F3 (4%). These results suggest that the tapak dara leaf extract gel lotion has strong potential as an effective herbal sunscreen with maximum protection.